2018
DOI: 10.1159/000487972
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Reduces Cardiac Interstitial Fibrosis by Inhibiting Erk1/2-Serpine2 and P-Akt Signalling Pathways

Abstract: Background/Aims: Cardiac interstitial fibrosis is an abnormality of various cardiovascular diseases, including myocardial infarction, hypertrophy, and atrial fibrillation, and it can ultimately lead to heart failure. However, there is a lack of practical therapeutic approaches to treat fibrosis and reverse the damage to the heart. The purpose of this study was to investigate the effect of long-term aspirin administration on pressure overload–induced cardiac fibrosis in mice and reveal the underlying mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Also, ERK1/2 inhibition attenuated fibrotic remodeling after myocardial infarction (Luo et al 2017 ). Although the structurally similar aspirin has been shown to suppress ERK1/2 and SMAD2/3 signaling (Li et al 2018 ; Zhang et al 2020 ), systemic side effects might overshadow the potential benefits. For this reason, we explored the effects of mesalazine on SMAD2/3 and ERK1/2 activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, ERK1/2 inhibition attenuated fibrotic remodeling after myocardial infarction (Luo et al 2017 ). Although the structurally similar aspirin has been shown to suppress ERK1/2 and SMAD2/3 signaling (Li et al 2018 ; Zhang et al 2020 ), systemic side effects might overshadow the potential benefits. For this reason, we explored the effects of mesalazine on SMAD2/3 and ERK1/2 activation.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly interesting, since NFκ B has been shown to induce myofibroblast differentiation and fibrosis in pulmonary and hepatic fibrosis (Luedde and Schwabe 2011; Dong and Ma 2019). SMAD2/3 and ERK1/2 activation by TGFβ are central mechanisms of the fibrotic signaling cascade (Khalil et al 2017;Khalil et al 2017;Luo et al 2017) and modulation of these pathways has been proposed to affect cardiac and non-cardiac fibrosis (Rosenbloom et al 2013;Cheng et al 2016;Khalil et al 2017;Li et al 2018). In a murine model of pressure overload, selective block of SMAD2/3 signaling drastically attenuated fibrosis (Khalil et al 2017).…”
Section: Mesalazine Acts As a Dual Inhibitor Of Smad2/3 And Erk1/2 Phmentioning
confidence: 99%
“…Aspirin can reduce cardiac interstitial fibrosis by inhibiting Erk1/2-Serpine2 and P-Akt signaling pathways [20]. In humans, there is evidence that aspirin may impair reverse myocardial remodeling in heart failure patients treated with beta blockers [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some studies on the application of aspirin as an anti-fibrosis treatment, the specific anti-fibrosis mechanism of aspirin remains unclear. Aspirin decreases cardiac interstitial fibrosis caused by pressure overload in transverse aortic constriction (TAc) mice, which may be associated with the inhibition of the p-Erk1/2 and p-Akt/β-catenin signalling pathways by aspirin, thereby decreasing the expression levels of α-SMA and collagen I (37). A previous study revealed that aspirin alleviated cardiac fibrosis in mice by inhibiting autophagy (22).…”
Section: Discussionmentioning
confidence: 99%